PHYSICAL ACTIVITY LEVEL, PERCEIVED BARRIERS AND FACILITATORS AMONG WOMEN IN NNEWI, ANAMBRA STATE (Journal of Biomedical Investigation, 2025)
Background: Physical inactivity is a major public health concern and a significant risk factor for non-communicable diseases, particularly among women in low- and middle-income countries where sociocultural and environmental demands may limit physical activity participation. Aim: This study assessed the levels of physical activity, perceived benefits, and perceived barriers to physical activity among adult women residing in Nnewi, Anambra State, Nigeria. Materials and methods: A cross-sectional study design involving 400 adult women selected from the four quarters of Nnewi was adopted. The International Physical Activity Questionnaire-Short Form (IPAQ-SF) assessed physical activity level, while the Exercise Benefits and Barriers Scale (EBBS) assessed perceived benefits and barriers. Data was summarized using frequency counts, charts, mean and standard deviation while the Kruskal-Wallis test was used for analysis at the
Keywords: Physical activity; Exercise benefits; Exercise barriers; Women; Sedentary behaviour; Nnewi; Nigeria